Legal Problems of Environmental Impact Assessment in Thailand Calling for Law Revision - Phothiruk, Darika (Faculty of Law, Hasanuddin University, 2021)
The Environmental Impact Assessment (EIA) is well-known and widely used as an essential tool for environmental management. Over the past 40Â years, there have been problems and obstacles in law enforcement and prosecutions in many cases under the EIA laws related to national development projects in Thailand. For this reason, this article aims to present the results of a study of the legal measures on the EIA process in Thailand. This study was conducted through reviewing concepts and theories concerning the EIA and related laws both in Thailand and abroad. The main objective of this study was to analyze the condition of problems and obstacles caused by attempts made in the law enforcement. The importance of the study would result in revision of the laws related to the EIA process to achieve sustainable development goals.